1990
DOI: 10.3109/02699059009026148
|View full text |Cite
|
Sign up to set email alerts
|

Return to work after rehabilitation following traumatic brain injury

Abstract: The relationship of medical variables and discharge functional status to vocational and educational outcomes was examined in 79 closed head-injured patients who were consecutively admitted to an inpatient rehabilitation hospital during a two-year period. A follow-up study, conducted after hospital discharge (median, 16.5 months), found that 66% (n = 52) of the patients had returned to work or school, while 34% (n = 27) did not. Patients were divided into return and non-return to work groups. Traditional variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
3

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(29 citation statements)
references
References 14 publications
2
24
0
3
Order By: Relevance
“…From a community re-integration perspective, the study also confirms that it is important to conduct ecologically oriented comprehensive wideranging cognitive and behavioural assessments to identify his cognitive strengths and weaknesses at the different stages of recovery, and to direct vocational treatment with behavioural predictive factors in mind. A satisfying outcome in terms of eventually re-acquired functional independence does not necessarily mean successfully competitive re-employment; this is in agreement with the generally sustained opinion affirming that, first cognitive, behavioural and emotional problems and, subsequently, physical deficits have a potentially negative effect on family and social integration [14,33].…”
Section: Discussionsupporting
confidence: 82%
“…From a community re-integration perspective, the study also confirms that it is important to conduct ecologically oriented comprehensive wideranging cognitive and behavioural assessments to identify his cognitive strengths and weaknesses at the different stages of recovery, and to direct vocational treatment with behavioural predictive factors in mind. A satisfying outcome in terms of eventually re-acquired functional independence does not necessarily mean successfully competitive re-employment; this is in agreement with the generally sustained opinion affirming that, first cognitive, behavioural and emotional problems and, subsequently, physical deficits have a potentially negative effect on family and social integration [14,33].…”
Section: Discussionsupporting
confidence: 82%
“…A brief review of return to work (RTW) literature reveals contradicting findings regarding the effect of injury severity on RTW [11][12][13]. RTW rates have been tied to injury severity [9,[13][14], although not all investigators have found a relationship between injury severity and RTW [12,[15][16].…”
Section: Introductionmentioning
confidence: 99%
“…RTW rates have been tied to injury severity [9,[13][14], although not all investigators have found a relationship between injury severity and RTW [12,[15][16]. Despite the varying results, it is important to note that some individuals who sustained very severe injuries are able to return to employment relatively unhindered [7,13].…”
Section: Introductionmentioning
confidence: 99%
“…Long-term debilitating behavioural change is common regardless of injury severity [18] and while return to work is clearly a laudable aim and has an obvious economic benefit, it represents an unrealistic goal for many [19][20][21][22][23]. Indeed many brain-injured adults have no constructive means of occupying their time [24,25].…”
Section: Introductionmentioning
confidence: 99%